EFEK KONDISI FINANSIAL, STRUKTUR UTANG, DAN CASH HOLDING PADA SENSITIVITAS ARUS KAS INVESTASI: Studi Kasus: Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2021 - Faiqoh, Dewi; Kustina, Lisa; Taftazani, Afif Mustafid (Jurnal Investasi, 2023)
This study aims to analyze the adaptation of companies before the pandemic to post-covid-19. Panel data regression with a fixed model. A sample of 30 companies was divided into two categories, namely companies that experienced problems and those that did not. The sampling technique uses purposive sampling analysis method, secondary data, and panel data with the help of the Eviews statistical tool. The results obtained are partially companies with financial condition (X1) and debt structure (X2) have a positive and significant effect on ICFS. cash holding has no effect on ICFS. Simultaneously the results of financial condition (X1), debt structure (X2), and cash holding (X3) affect the investment cash flow sensitivity variable (Y). Keywords: financial condition, debt structure, cash holding, and investment cash flow sensitivity.